(untitled) (New Jesey, NJ, 2002)
Proceedings of the 7th IEEE Intl Workshop, held July 22-24, 2002 in Frankfurt, Germany. Covers the fundamental theory as well as the applications in various fields such as science and technology in cellular neural networks.
Keywords: Cellular neural networks,Neural networks (Computer science) |v Congresse; Applied physics,Mạng lưới tế bào thần kinh; Nonlinear information processing